Hubungan antara Kebiasaan Merokok dengan Angka Kejadian Lesi yang Diduga Stomatitis Nikotina pada Masyarakat Desa Ongkaw Dua - Tambunan, Miranda A.; Suling, Pieter L.; Mintjelungan, Christy N. (e-CliniC, 2019)
Abstract: Nicotine stomatitis could be found among heavy smokers. This study was aimed to determine the relationship between smoking habits and the incidence of lesions suspected as nicotine stomatitis among villagers of Ongkaw Dua. This was an analytical study with a cross sectional design. Population consisted of 183 smokers aged >15 years at Desa Ongkaw Dua and the subjects were 65 smokers. The chi-square showed a p-value of 0.592 for the relationship between the duration of smoking and the occurence of lesion supspected as nicotine stomatitis. Moreover, the chi-square showed a p-value of 0.005 for the relationship between the number of cigarettes consumed per day and the occurence of lesion suspected as nicotine stomatitis. In conclusion, there was no relationship between the duration of smoking and the occurence of lesion suspected as nicotine stomatitis, but there was a significant relationship between the number of cigarettes consumed per day and the occurence of lesion suspected as nicotine stomatitis.Keywords: smoking habit, nicotine stomatitisÂ Abstrak: Stomatitis nikotina dapat dijumpai pada perokok berat. Penelitian ini bertujuan untuk mengetahui hubungan antara kebiasaan merokok dengan angka kejadian lesi yang diduga stomatitis nikotina pada masyarakat desa Ongkaw Dua. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Populasi penelitian ini yaitu 183 perokok berusia >15 tahun di Desa Ongkaw Dua dan yang menjadi subyek penelitian berjumlah 65 orang. Hasil uji chi-square terhadap hubungan lama merokok dengan angka kejadian lesi yang diduga stomatitis nikotina mendapatkan p=0,592. Hasil uji chi-square terhadap hubungan antara jumlah rokok yang dihisap setiap hari dengan angka kejadian lesi yang diduga stomatitis nikotina mendapatkan p=0,005. Simpulan penelitian ini ialah tidak terdapat hubungan antara lamanya merokok dengan angka kejadian lesi yang diduga stomatitis nikotina, tetapi terdapat hubungan bermakna antara jumlah rokok yang dihisap setiap hari dengan angka kejadian lesi yang diduga stomatitis nikotina.Kata kunci: kebiasaan merokok, stomatitis nikotina